Renegotiation Costs and Debt Contract Design - Dyreng, Scott D.; Ferracuti, Elia; Morris, Arthur K. (The Accounting Review, 2025)
ABSTRACT We examine the relation between debt contract renegotiation costs and contract design. We use a plausibly exogenous shock to expected renegotiation costs arising from a change in the taxation of debt renegotiations to show that, as renegotiation costs decline, the maturity of debt contracts lengthens, the initial likelihood of covenant violation increases, and the use of performance pricing provisions becomes less frequent. The evidence indicates that ex ante allocation of cash flow rights and ex post reallocation of decision rights through renegotiation are local substitutes, where the preference for one mechanism versus the other depends, at least in part, on renegotiation costs. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G32; G33; G38.